Typhoid Fever among Admitted Pediatric Patients in a Tertiary Care Center: A Descriptive Cross-sectional Study - Gajendra Prasad Rauniyar (Journal of Nepal Medical Association, 2021)
Introduction: Typhoid fever, an acute systemic febrile illness caused by Salmonella Typhi & Paratyphi, is an important public health problem in developing countries. It requires frequent observation regarding proper diagnostic protocol and treatment practices. The aim of the study is to find the prevalence of typhoid fever among admitted pediatric patients in a tertiary care center.